(untitled) - Page, Bruce (Garden City, New York, 1968)
Non of you is yet equal to the dimensions scandal. Like a great novel, and an unfinished one at that, Kim Philby lives on in us
Keywords: Espionage, Soviet,Spies; Great Britain; Biography; Great Britain